Community structure of meifauna in razor clam area - Imelda, Joanes (Universiti Malaysia Sarawak (UNIMAS), 2005)
The study on meiofauna community structure in the Razor clam area was conducted at two intertidal beaches of Kampung Asajaya Laut (Station 1) and Kampung Pasir Puteh (Station 2). From both stations, a total of 18 meiofauna taxa were identified. The assemblages were largely dominated by Nematoda, except for the few plots in the transect range from Mean Low Water Neap to Mid Tide Level to Mean High Water Neap at Station 2 which is dominated by Copepoda. The meiofauna community structure of both areas appears to be determined primarily by pH, temperature and salinity. Total average density of meiofauna in Station 1 was 239.69 individuals per 10cm2 and 238.68 individuals per 10cm2 in Station 2. Nematoda (46.88 individuals per IOcm2) dominated the total density of meiofauna in Razor clam area at Station 1, whilst Copepoda (38.26 individuals per 10cm2) and Nematoda (34.29 individuals per 10cm2) equally dominate the Razor clam area at Station 2. The findings of the tudy can assist future environmental studies in the respective area.